Shapes and sizes to safety: Labour delivery room design as case study - Mohd Nawawi, Norwina (2011)

(untitled)
Every so often architects design spaces for proposed facilities based on space standards stated in guidelines or listed as schedule of accommodation (SOA) of a project brief. Process of design through formation of spaces and relationship layouts were created intuitively through experience, integrating structural grids, circulation spaces and functional spaces based on centre to centre dimension. In healthcare facility design where size and configuration is critical in determining efficiency of the purported function for SAFETY (from cross infection and accident), the subject of appropriate shape and size need to be understood and interweave in the decision making. A case study, through observation and onsite measurement, were conducted on selected labour delivery room designs where different architect interpreted the same requirements of the Malaysian public hospital project brief, differently. Findings reveal choices of structural grids, building forms and the different decision makers (design team and users) on its utilisation/operation pre and post design, have effects on safety of the users(patient, staff and visitors) if they are not careful. However, Man, as adaptable being through behavioural studies, showed constraints makes them more careful. Thus incite an onward inquiry whether the bigger the space and of a certain shape the better safety precaution are or the tighter the space as being more appropriate! Hence the inquiry on the critical dimension set forth.